2019
DOI: 10.1177/0033294119843224
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Test Anxiety With an Invariant Measure Across Genders: The Case of the German Test Anxiety Inventory

Abstract: Since test performance is increasingly relevant in educational and occupational circles, the assessment of test anxiety—the phenomenological, physiological, and behavioral responses to the negative consequences that often emerge in evaluative situations—has become increasingly important to scholars and practitioners. One of the most widely employed scales to measure test anxiety in adolescents is the German Test Anxiety Inventory (in German: Prufungsangstfragebogen, PAF). The current study investigated the psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 60 publications
5
11
0
1
Order By: Relevance
“…In terms of gender differences, previous research confirmed measurement invariance with regards to factor loadings for the German (Raufelder and Ringeisen 2016;Ringeisen et al 2016), the English (Hoferichter et al 2016;Mowbray et al 2014), and the Italian PAF (Donati et al 2019), although level differences emerged: Women, compared to men, reported higher scores across most subscales, with quantity and quality of these patterns varying slightly from study to study. These gender differences corroborate results from cross-cultural research, which consistently identified women to report higher test anxiety scores irrespective of the test anxiety facet (see Tibubos et al 2020, in this volume;von der Embse et al 2018;Zeidner 2007).…”
Section: The German Test Anxiety Questionnaire (Paf) and Its English mentioning
confidence: 81%
See 2 more Smart Citations
“…In terms of gender differences, previous research confirmed measurement invariance with regards to factor loadings for the German (Raufelder and Ringeisen 2016;Ringeisen et al 2016), the English (Hoferichter et al 2016;Mowbray et al 2014), and the Italian PAF (Donati et al 2019), although level differences emerged: Women, compared to men, reported higher scores across most subscales, with quantity and quality of these patterns varying slightly from study to study. These gender differences corroborate results from cross-cultural research, which consistently identified women to report higher test anxiety scores irrespective of the test anxiety facet (see Tibubos et al 2020, in this volume;von der Embse et al 2018;Zeidner 2007).…”
Section: The German Test Anxiety Questionnaire (Paf) and Its English mentioning
confidence: 81%
“…Recently, an Italian version of the PAF was published based on an adolescent sample (Donati et al 2019). Although the Italian version mirrors the favorable psychometric properties of the other two language versions at first sight, a closer look reveals a number of problems.…”
Section: The German Test Anxiety Questionnaire (Paf) and Its English mentioning
confidence: 99%
See 1 more Smart Citation
“…Ademais, seria importante diversificar as amostras, tendo em conta diferentes grupos de estudantes, devendo-se considerar diferentes níveis educacionais, a exemplo do ensino fundamental e médio, além de estudantes de pós-graduação (especialização, mestrado e doutorado), pois pode ser útil comparar participantes de diferentes faixas etárias que estão em distintos estágios do processo educativo (Donati et al, 2019).…”
Section: Discussionunclassified
“…Having good psychometric properties (Donati et al 2019;Hodapp et al 2011;Hoferichter et al 2015;Schnell et al 2013), the PAF has become one of the most widely used questionnaires to assess test anxiety in German and has been adapted to English (Hoferichter et al 2015) and Italian (Donati et al 2019).…”
Section: Differentiating Between Cognitive Facetsmentioning
confidence: 99%